Application of Bed Load Formulations for Dam Failure and Overtopping - Seyed Alireza Hosseinzadeh-Tabrizi; Mahnaz Ghaeini-Hessaroeyeh (Civil Engineering Journal, 2017)
The Enhanced HLLC scheme as a robust approximate Riemann solver is used for numerical modeling of three different test cases of mobile bed and stepped mobile bed in dam failure and dam overtopping conditions. The current research has been done in the frame of the finite volume method using shallow water equations along with the Exner equation for sediment continuity. The Ribberink, Wong and Parker formulations have been used for the modelling of bed load movement. A convenient approach based on the Boussinesq hypothesis is deployed for considering turbulence effects in the second case. The affections of stepped and slope condition for the flow bed are considered through a corrected version of the HLLC flux components. Finally, the model is applied for modelling overtopping in the third case. The results of the present model are relatively reasonable by comparing with the experimental data.